Latin American Entrepreneurs : Many Firms but Little Innovation - Lederman, Daniel (Washington, DC: World Bank, 2014)
Entrepreneurship is a fundamental driver of growth, development, and job creation. While Latin America and the Caribbean has a wealth of entrepreneurs, firms in the region, compared to those in other regions, are small in size and less likely to grow or innovate. Productivity growth has remained lackluster for decades, including during the recent commodity boom. Enhancing the creation of good jobs and accelerating productivity growth in the region will require dynamic entrepreneurs.